Analisis Penyusunan Rencana Anggaran Pendanaan Satuan Pendidikan Islam:Kajian Opersional dan Teknis - Anis Fitria; Haitsam Haitsam; Mardiyah Mardiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Budget planning in Islamic educational institutions is a crucial factor in ensuring the sustainability and effectiveness of financial management. This article analyzes the strategies for preparing budget plans in Islamic educational institutions from operational and technical perspectives. Proper planning ensures the optimal allocation of resources to support the learning process, facility maintenance, and quality improvement in education. This study highlights the importance of transparency, accountability, and the use of performance-based approaches in budget management. Additionally, government regulations, stakeholder involvement, and the utilization of technology are key factors in enhancing the efficiency and effectiveness of budget planning in Islamic education. The findings of this study are expected to provide insights for Islamic education administrators in developing a more structured and sustainable financial strategy.